2020
DOI: 10.3390/nu12103098
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Food Containing Paramylon Derived from Euglena gracilis EOD-1 on Fatigue in Healthy Adults: A Randomized, Double-Blind, Placebo-Controlled, Parallel-Group Trial

Abstract: Euglena gracilis EOD-1, a kind of microalgae, is known to contain a high proportion of paramylon, a type of β-1,3-glucan. Paramylon derived from E. gracilis EOD-1 is presumed to suppress cellular oxidative injury and expected to reduce fatigue and fatigue sensation. Therefore, we aimed to examine whether food containing paramylon derived from E. gracilis EOD-1 (EOD-1PM) ingestion reduced fatigue and fatigue sensation in healthy adults. We conducted a randomized, double-blind, placebo-controlled, parallel-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…With regard to carbohydrate production, these values are consistent with those previously reported, where the microalgae could accumulate around 20% of carbohydrates [ 35 ], being its second major component. In the case of euglenoids, which are capable of accumulating high quantities of paramylon [ 36 ], or in Skeletonema costatum, which accumulate β-glucans as an energy reservoir [ 37 ], it has been suggested that there is a mechanism that diminishes its metabolisms and focuses in accumulate reserve metabolites to maintain cell viability. The full metabolic activities return once the nutrients are restored to requirement levels by the microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to carbohydrate production, these values are consistent with those previously reported, where the microalgae could accumulate around 20% of carbohydrates [ 35 ], being its second major component. In the case of euglenoids, which are capable of accumulating high quantities of paramylon [ 36 ], or in Skeletonema costatum, which accumulate β-glucans as an energy reservoir [ 37 ], it has been suggested that there is a mechanism that diminishes its metabolisms and focuses in accumulate reserve metabolites to maintain cell viability. The full metabolic activities return once the nutrients are restored to requirement levels by the microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that EOD‐1 reduces fatigue by improving antioxidant potential (Kawano et al, 2020 ). PM has been reported to reduce oxidative damage to cells, improve oxidatively induced liver damage in rats, and increase liver reductase activity (Sugiyama et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Beta‐glucans are common in cereal grains, fungi, and algae, although their physicochemical properties vary considerably from source to source. Recent studies indicate the positive effects of PM supplements in terms of reducing fatigue and promoting immune function (Ishibashi et al, 2019 ; Kawano et al, 2020 ). However, to date, no human intervention study investigating the anti‐obesity effects of PM has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A 12-week study showed that consuming EG had positive effects on reducing tension and easing irritability associated with performing stressful mental tasks [13]. A 4-week trial showed a significantly lower level of taskinduced mental fatigue and a higher level of work efficiency when compared to the placebo group [14].…”
Section: Introductionmentioning
confidence: 99%